Fungsi Mantra Cenningrara dalam Meningkatkan Motivasi Hidup Orang Bugis Soppeng - Arjuna, Muhammad Gusri; Aj, Andi Agussalim; Junus, Andi Fatimah (SOCIETIES: Journal of Social Sciences and Humanities, 2023)
Abstract: The Function of the Cenning Rara Mantra in Increasing the Life Motivation of the Bugsi Soppeng People. Thesis, Department of Indonesian Language and Literature, Faculty of Language and Literature, State University of Makassar (supervised by Andi Agussalim Aj and andi Fatimah Yunus) This study aims to describe the function of the cenning rara mantra in increasing the motivation of the Soppeng Bugis people's lives. This type of research is qualitative with a descriptive design. The data in this study are the cenning rara mantra, oral data, sentences containing the function of the mantra and the relationship between the mantra and motivation in life which comes from informants, namely the Soppeng people who were interviewed. The data in this study used interview, observation, and documentation techniques. The results of this study indicate that there is a function of mantra and a relationship between mantra and motivation in life, namely (1) the function of mantra as a means of entertainment, (2) the function of mantra as a means of validating cultural institutions, (3) the function of mantra as a means of teaching and education and, (4) the function of spells as a means of coercing and supervising customs rules. The relationship between the mantra and the life motivation of the Soppeng Bugis people are (1) the value of the function of the spell related to humans, (2) the value of the function of the spell related to oneself, (3) the value of the function of the spell related to nature and, (4) the value of the function related to relate to God. Keywords: Cenning rara, spell function